Method for electrocatalytic hydrogenation of lignin by using Bi-(Et3N) catalyst

By using Bi-(Et3N) catalyst and optimizing its structure through crystal phase reconstruction strategy, the problem of low conversion efficiency during lignin electrochemical reduction is solved, and efficient lignin electrochemical hydrogenation conversion and excellent phenol selectivity are achieved.

CN119824470AActive Publication Date: 2025-04-15INST OF CHEM IND OF FOREST PROD CHINESE ACAD OF FORESTRY

Patent Information

Application Number
CN202510070621.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-15
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

The conversion efficiency of existing lignin is low during electrochemical reduction process, the catalyst depends on precious metals, poor product selectivity, high economic cost, and the process of preparing multifunctional catalysts is complicated.

Method used

Bi-(Et3N) catalyst is used to adjust the defect site and electron-deficient metal content in the catalyst structure through crystal phase reconstruction strategy, and optimize the microcosmic coordination environment to improve catalytic efficiency.

Benefits of technology

The efficient conversion of electrochemical hydrogenation of lignin model substances was achieved, the reaction potential and kinetic efficiency were optimized, and the selectivity of phenol was significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824470A_ABST
    Figure CN119824470A_ABST
Patent Text Reader

Abstract

The invention discloses a method for electro-catalytic hydrogenation of lignin by using a Bi-(Et3N) catalyst, and belongs to the technical field of electro-catalytic hydrogenation of lignin. The method comprises the following steps: adding a Bi-(Et3N) catalyst and a lignin model compound into an H-shaped electrolytic cell, and carrying out electro-catalytic hydrogenation on the model compound under a constant current system. In the preparation process of the catalyst, the coordination environment of Bi < 3 + > species is changed by adjusting the use amount of triethylamine, so that controllable transformation between Bi (OH) 3 and Bi-(N-C) coordination structures is realized, a large number of lattice defects are further derived, the generation of the Bi-(N-C) structures induces the appearance of electron-deficient Bi species, and the yield of the catalyst is improved. The electrochemical hydrogenation catalyst shows excellent performance in electrochemical hydrogenation of lignin model compounds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lignin electrocatalytic hydrogenation, and specifically relates to a method for electrocatalytic hydrogenation of lignin using a Bi-(Et3N) catalyst. Background Art

[0002] Efficiently converting abundant renewable biomass resources into high-value-added chemicals and fuels is considered a promising strategy to alleviate the dilemma of excessive consumption of fossil energy. As a typical component of biomass, lignin is the most abundant phenolic polymer in nature. Bonds are the main connecting bonds in the lignin structure. The key to achieving efficient and directional conversion of lignin is the efficient and selective cracking technology of lignin bonds. Electrocatalytic hydrogenation has attracted extensive attention due to its environmental compatibility and high reaction efficiency. However, due to the stubborn three-dimensional network of lignin, existing electrocatalytic systems usually exhibit high reaction potential and low kinetic efficiency, and the occurrence of competitive hydrogen evolution reaction is not conducive to the overall Faradaic efficiency.

[0003] Among the strategies for directed cracking of lignin model compounds that have been developed, defect engineering of catalysts has shown great potential in optimizing the adsorption and activation of reaction intermediates and achieving selective cracking. In addition, electron-deficient metal sites have shown great application prospects in electrochemical systems due to their abundant electron vacancies, thus providing an advanced means to optimize electrochemical kinetic efficiency.

[0004] At present, the electrochemical reduction process of lignin has the problem of low conversion efficiency. The existing catalytic process strongly relies on precious metal catalysts, including commercial Pt / C, Rh / C, etc., but due to their single active site and uncontrollable hydrogenation process, they lead to poor product selectivity and high economic cost. The existing preparation of multifunctional catalysts with rich defects and electron-deficient metal sites often adopts heteroatom doping, surface etching, carbon encapsulation coating and other means, which often require complex and sophisticated preparation processes. In addition, the complex multi-structure leads to unclear coordination mode and unclear catalyst active center. Summary of the invention

[0005] A technical problem solved by the present invention is to provide a method for electrocatalytic hydrogenation of lignin using a Bi-(Et3N) catalyst, using a multifunctional Bi-(Et3N) catalyst rich in defect sites and electron-deficient metal species to electrocatalytically hydrogenate lignin; through a crystal phase reconstruction strategy, the microscopic coordination environment is adjusted to control the concentration of defect sites in the catalyst structure and the electron-deficient metal content is controllably adjusted, showing excellent performance in the electrochemical hydrogenation of a lignin model substance.

[0006] Technical solution: In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0007] The method of electrocatalytic hydrogenation of lignin using Bi-(Et3N) catalyst is as follows: Bi-(Et3N) catalyst is added into an "H" type electrolytic cell, and the lignin model is electrocatalytically hydrogenated under a constant current system.

[0008] In the method, the lignin is a lignin model substance 2-phenoxy-1-phenylethanol, and the mass ratio of the model substance to the catalyst is 0.4:1-5:1; preferably, the mass ratio of the model substance to the catalyst is 0.4:1-3:1.

[0009] The method has a current density of 20 to 60 mA cm -2 Preferably, the current density is 40 mA cm -2 .

[0010] In the method, the electrolytic cell uses a graphite rod as a working electrode, a Pt sheet as a counter electrode, Ag / AgCl as a reference electrode, a phosphotungstic acid solution as a cathode electrolyte, and phosphoric acid as an anode electrolyte.

[0011] In the method, the concentration of the phosphotungstic acid electrolyte is 0.25 M, and the concentration of phosphoric acid is 0.2 M; preferably, the concentrations of the phosphotungstic acid and phosphoric acid solutions are 11 mL respectively.

[0012] In the method, the temperature of the electrochemical hydrogenation process is 80-100° C. and the time is 1.5-3 hours; preferably, the temperature is 80° C. and the time is 1.5 hours.

[0013] The method, the preparation of the catalyst Bi-(Et3N), comprises the following steps:

[0014] (1) Dissolve the metal Bi salt in deionized water, slowly add triethylamine, and stir overnight to obtain a milky white precipitate;

[0015] (2) Transfer all the reaction liquid into a reactor, heat it in an air atmosphere, and then age and crystallize it;

[0016] (3) After washing and centrifugation, a white precipitate was obtained, which was then dried in vacuum to obtain the heterogeneous Bi-(Et3N) catalyst.

[0017] In the method, in step (1), the metal Bi salt is Bi(NO3)3-5H2O, the precipitant is triethylamine, and alkaline media such as urea and sodium hydroxide with the same pH value cannot form a heterogeneous structure; the molar ratio of the metal Bi salt to triethylamine is 1:3~1:5, and too much or too little triethylamine concentration will cause the Bi(OH)3 structure and the Bi-(NC) structure to collapse.

[0018] In the method, in step (2), the heating temperature is 90-100°C and the heating time is 6 hours; preferably, the heating temperature is 95°C.

[0019] In the method, the vacuum drying temperature in step (3) is 60° C. and the drying time is 12 hours.

[0020] Beneficial effects: Compared with the prior art, the present invention has the following advantages:

[0021] (1) The present invention uses alkaline triethylamine as a medium to react with OH + Capture Bi 3+ The species obtained a layered Bi(OH)3 main structure. Further, the N-containing coordination with the metal Bi 3+ Species chelate and change Bi 3+ The coordination environment of the species realizes the phase transition from Bi(OH)3 structure to Bi-(NC) structure during the aging crystallization process. + with Bi 3+ Chelation is used to realize the crystal phase reconstruction process, evolving a large number of lattice defect sites. In addition, the presence of Bi-(NC) induces the massive generation of electron-deficient Bi species, with a simple preparation process and strong structural controllability.

[0022] (2) The abundant defect sites in the heterogeneous Bi-(Et3N) catalyst of the present invention promote the adsorption of reaction intermediates, while the electron-deficient metal sites ensure the rapid activation of hydrogen protons in the system. This greatly solves the problem of high reaction potential and slow kinetics in the electrochemical hydrogenation of the lignin model material. In addition, it exhibits excellent selectivity for phenol. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is the X-ray diffraction pattern (XRD) of the Bi-(Et3N) catalyst prepared in Examples 1-2 and Comparative Examples 1-3;

[0024] Figure 2 is a transmission electron microscope (TEM) image of the Bi-(Et3N) catalyst prepared in Example 1;

[0025] Figure 3 is the element mapping diagram of the Bi-(Et3N) catalyst prepared in Example 1;

[0026] Figure 4 is an X-ray photoelectron spectroscopy (XPS) graph of the Bi-(Et3N) catalyst prepared in Examples 1-2 and Comparative Example 1;

[0027] Figure 5 is the electron paramagnetic resonance (EPR) graph of the Bi-(Et3N) catalyst prepared in Examples 1-2 and Comparative Example 1;

[0028] Figure 6 is a gas chromatography (GC) graph of the product obtained by electrochemical hydrogenation of the lignin model substance in Examples 3 and 4 and Comparative Example 4;

[0029] Figure 7 Graphs showing the yield and conversion rate of electrochemical hydrogenation of lignin model substances in Examples 3 and 4 and Comparative Example 4;

[0030] Figure 8 It is a linear sweep voltammetry (LSV) diagram of the electrochemical hydrogenation of the lignin model material in Examples 3, 4 and Comparative Example 4. DETAILED DESCRIPTION

[0031] The present invention is further illustrated below in conjunction with specific examples. The examples are implemented based on the technical solutions of the present invention. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0032] The calculation formula for the conversion rate of the lignin model substance of the present invention is as follows.

[0033] Conversion rate (%) = (initial amount of model substance - remaining amount of model substance after reaction) / initial amount of model substance × 100%;

[0034] Example 1

[0035] The preparation of the catalyst Bi-(Et3N) comprises the following steps:

[0036] (1) Dissolve 0.005 mol of bismuth nitrate pentahydrate in 50 mL of deionized water, and slowly add 0.015 mol of triethylamine. The pH value is 12.45. The solution becomes turbid. After continuous stirring at 800 rpm overnight, a milky white precipitate is obtained.

[0037] (2) Transfer all of the above 50 mL of reaction solution into a high temperature and high pressure reactor, and heat to 95°C for aging and crystallization under air atmosphere while stirring at 800 rpm for 6 hours;

[0038] (3) The emulsion after the reaction was centrifuged to obtain a white precipitate, which was washed three times with deionized water and further vacuum dried to obtain a heterogeneous Bi-(Et3N) catalyst.

[0039] Example 2

[0040] The preparation of the catalyst Bi-(Et3N) comprises the following steps:

[0041] (1) Dissolve 0.005 mol of bismuth nitrate pentahydrate in 50 mL of deionized water, and slowly add 0.025 mol of triethylamine. The pH value is 11.30. The solution becomes turbid. After continuous stirring at 800 rpm overnight, a milky white precipitate is obtained.

[0042] (2) Transfer all of the above 50 mL of reaction solution into a high temperature and high pressure reactor, and heat to 95°C for aging and crystallization under air atmosphere while stirring at 800 rpm for 6 hours;

[0043] (3) The emulsion after the reaction was centrifuged to obtain a white precipitate, which was washed three times with deionized water and further vacuum dried to obtain a heterogeneous Bi-(Et3N) catalyst.

[0044] Comparative Example 1

[0045] For comparison, the catalyst was synthesized at a low triethylamine concentration, and the molar ratio of the metal Bi salt to triethylamine was 1:1.

[0046] 0.005 mol of bismuth nitrate pentahydrate was dissolved in 50 mL of deionized water, and 0.005 mol of triethylamine was slowly added dropwise, pH = 12, the solution became turbid, and a milky white precipitate was obtained after continuous stirring at 800 rpm overnight.

[0047] Transfer all of the above 50 ml reaction solution into a high temperature and high pressure reactor, heat to 95°C for aging and crystallization while stirring at 800 rpm in an air atmosphere, and keep it for 6 hours;

[0048] Finally, the emulsion after the reaction was centrifuged to obtain a white precipitate, which was washed three times with deionized water and further vacuum dried to obtain Bi-(OH)3.

[0049] Comparative Example 2

[0050] For comparison, the catalysts were synthesized with different precipitants at pH = 12, and the molar ratio of metal Bi salt to urea was 1:5.

[0051] 0.005 mol of bismuth nitrate pentahydrate was dissolved in 50 mL of deionized water, and 0.025 mol of urea was slowly added. The solution became turbid and a milky white precipitate was obtained after continuous stirring at 800 rpm overnight.

[0052] Transfer all of the above 50 ml reaction solution into a high temperature and high pressure reactor, heat to 95°C for aging and crystallization while stirring at 800 rpm in an air atmosphere, and keep it for 6 hours;

[0053] Finally, the emulsion after the reaction was centrifuged to obtain a white precipitate, which was washed three times with deionized water and further vacuum dried to obtain Bi-(CO(NH2)2).

[0054] Comparative Example 3

[0055] For comparison, the catalyst was synthesized using sodium hydroxide as a precipitant at pH = 12, and the molar ratio of the metal Bi salt to sodium hydroxide was 1:5.

[0056] 0.005 mol of bismuth nitrate pentahydrate was dissolved in 50 mL of deionized water, and 0.025 mol of sodium hydroxide was slowly added. The solution became turbid and a milky white precipitate was obtained after continuous stirring at 800 rpm overnight.

[0057] Transfer all of the above 50 ml reaction solution into a high temperature and high pressure reactor, heat to 95°C for aging and crystallization while stirring at 800 rpm in an air atmosphere, and keep it for 6 hours;

[0058] Finally, the emulsion after the reaction was centrifuged to obtain a white precipitate, which was washed three times with deionized water and further vacuum dried to obtain Bi-(NaOH).

[0059] The catalysts prepared in Examples 1-2 and Comparative Examples 1-3 were characterized and analyzed, and the results were as follows:

[0060] like Figure 1 As shown, the crystal phase composition of the catalyst was analyzed by XRD. It can be seen from the XRD spectra corresponding to Examples 1-2 and Comparative Examples 1-3 that the catalysts prepared in Comparative Examples 1-3 are mainly Bi(OH)3 species, and no Bi-(NC) structure was detected. In the XRD spectra corresponding to Examples 1 and 2, obvious characteristic diffraction peaks corresponding to Bi2O3 can be found. And at 2θ = 14.9 o ,35.0 o and 41.3 o A new diffraction peak appears at + Ions and Bi 3+ The species chelate, and then the Bi-(NC) coordination structure is obtained after aging and crystallization.

[0061] like Figure 2 As shown, the morphology and crystal properties of the Bi-(Et3N) catalyst were analyzed by TEM. Figure 2 As shown in Figs. a and 2b, Example 1 exhibits a regular lamellar crystal structure. In addition, the lattice fringe spacings of 0.205 nm and 0.338 nm observed in the high-resolution transmission electron microscopy (HR-TEM) images are attributed to Bi(OH)3 ( Figure 2 c and 2d). The halo patterns detected in the selected area electron diffraction (SAED) are attributed to the crystal planes of Bi2O3 ((203), (321), (324)) and Bi6O5(OH)3(NO3)5(H2O)3, indicating the presence of a polycrystalline composite structure ( Figure 2 e). Note that no Bi(OH)3 structure is detected in the diffraction rings, which is because the Bi(OH)3 structure is extensively oxidized and reconstructed. Irregular and disordered fringe spacing is also found in the TEM results corresponding to Example 1, which is caused by the formation of metastable structures. Therefore, these phenomena indicate that the structural composition of the Bi-(Et3N) catalyst is mainly composed of Bi2O3-Bi(OH)3 complexes, accompanied by the presence of metastable Bi-(NC) coordination structures generated by chelation of Bi and -NC- groups.

[0062] From the element mapping diagram ( Figure 3 ), Bi, O, N and C are uniformly distributed throughout the catalyst obtained in Example 1. The overlapping distribution of these elements suggests that N and C exist in the lattice of the bismuth-based oxide in the form of a coordination structure.

[0063] like Figure 4 The XPS spectrum of the Bi-(Et3N) catalyst is shown in Figure 2. Figure 4 As shown in a, the presence of Bi, O, N, and C species can be clearly detected, proving the existence of a multiphase structure. Due to the spin-orbit splitting, Bi 4f has two contributions in the XPS spectrum: 4f 7 / 2 and 4f 5 / 2 For Comparative Example 1 ( Figure 4 b) The peaks at 158.6 and 163.8 eV belong to the Bi in the Bi6O5(OH)3(NO3)5(H2O)3 structure. 3+ , while the peaks at 160.0 and 165.3 eV belong to Bi(OH)3 3+ For Example 1, two peaks were added at 161.2 and 166.3 eV binding energies, corresponding to the appearance of electron-deficient high-valent Bi species. This is due to the protonated -NC- group and Bi 3+ The electron transfer between the two leads to the electron deficiency of metallic Bi. In addition, through the fitting integration of the XPS peak, with the increase of triethylamine concentration, in Example 2, the electron-deficient Bi species is relative to Bi 3+ The ratio of N 1s is further increased. For the XPS spectrum of N 1s, a peak corresponding to the Bi-N structure is found at 406.3 eV ( Figure 4c), proving that there is an interaction between N element and Bi metal, where N species can accept Bi electrons. In addition, the C 1s spectrum at around 285.2, 287.3 and 288.7 eV ( Figure 4 d) are divided into sp 3 Carbon, -NC- and π-π* coordination modes. These results show that in addition to the Bi-O bond, the coordination mode of Bi species also exists in the form of Bi-N, and there is no Bi-C coordination mode. This further proves that the composite phase of Bi(OH)3-Bi2O3 and Bi-(NC) appears in Example 1-2. At the same time, as the molar concentration of triethylamine to metal Bi salt increases from 1:3 to 1:5, the relative ratio of Bi-NC coordination increases further. It shows that the degree of transformation of the crystal structure can be achieved by adjusting the concentration of triethylamine.

[0064] like Figure 5 As shown, the defect site content in the catalyst was detected by EPR. Examples 1-2 all showed obvious signal intensity at g = 2.0003, and were higher than that of Comparative Example 1, indicating that the appearance of the polycrystalline composite structure and the Bi-(NC) coordination structure produced abundant lattice defects.

[0065] Example 3

[0066] Electrocatalytic hydrogenation of 2-phenoxy-1-phenylethanol using the Bi-(Et3N) catalyst prepared in Example 1:

[0067] An "H" type electrolytic cell was used, with a graphite rod as the working electrode, a Pt sheet as the counter electrode, and Ag / AgCl as the reference electrode. A 0.25 M phosphotungstic acid solution was used as the cathode electrolyte, and a 0.2 M phosphoric acid solution was used as the anode electrolyte. The phosphotungstic acid and phosphoric acid solutions were 11 mL each. A constant current system was used, and the current density was 40 mA cm -2 0.02 g of catalyst and 0.069 g of 2-phenoxy-1-phenylethanol were added for electrochemical hydrogenation. The temperature was set at 80° C. and the electrolysis time was maintained for 1.5 hours.

[0068] The results are as follows Figure 6 As shown in Figure 7, the catalyst prepared in Example 1 catalyzed the production of four products, namely phenol (2a), 1-phenylethanol (3a) and acetophenone (4a), with a conversion rate of up to 93.23%, showing excellent conversion performance. In addition, it can be seen from the corresponding linear sweep voltammetry curve ( Figure 8 ), 100 mA cm can be obtained at low potential -2 The current density of 2.5 W was 0.1 W, which proves that the catalyst has excellent electrochemical performance.

[0069] Example 4

[0070] The electrocatalytic hydrogenation of 2-phenoxy-1-phenylethanol was carried out using Bi-(Et3N) prepared in Example 2 as a catalyst:

[0071] An "H" type electrolytic cell was used, with a graphite rod as the working electrode, a Pt sheet as the counter electrode, and Ag / AgCl as the reference electrode. A 0.25 M phosphotungstic acid solution was used as the cathode electrolyte, and a 0.2 M phosphoric acid solution was used as the anode electrolyte. The phosphotungstic acid and phosphoric acid solutions were 11 mL each. A constant current system was used, and the current density was 40 mA cm -2 0.02 g of catalyst and 0.069 g of 2-phenoxy-1-phenylethanol were added for electrochemical hydrogenation. The temperature was set at 80° C. and the electrolysis time was maintained for 1.5 hours.

[0072] The results are as follows Figure 6 As shown in Figure 7, the catalyst prepared in Example 2 catalyzed the production of four products, namely, phenylethanol (1a), phenol (2a), 1-phenylethanol (3a) and acetophenone (4a), with a conversion rate of up to 99.04%, showing excellent conversion performance. In addition, it can be seen from the corresponding linear sweep voltammetry curve ( Figure 8 ), 100 mA cm can be obtained at low potential -2 The current density of 2.5 W was 0.1 W, which proves that the catalyst has excellent electrochemical performance.

[0073] Comparative Example 4

[0074] Electrocatalytic hydrogenation of 2-phenoxy-1-phenylethanol using the catalyst prepared in Comparative Example 1:

[0075] An "H" type electrolytic cell was used, with a graphite rod as the working electrode, a Pt sheet as the counter electrode, and Ag / AgCl as the reference electrode. A 0.25 M phosphotungstic acid solution was used as the cathode electrolyte, and a 0.2 M phosphoric acid solution was used as the anode electrolyte. The phosphotungstic acid and phosphoric acid solutions were 11 mL each. A constant current system was used, and the current density was 40 mA cm -2 0.02 g of catalyst and 0.069 g of 2-phenoxy-1-phenylethanol were added for electrochemical hydrogenation. The temperature was set at 80° C. and the electrolysis time was maintained for 1.5 hours.

[0076] The results are as follows Figure 6 , as shown in Figure 7, the catalyst prepared in Comparative Example 1 catalyzed the production of three products, namely, phenylethanol (1a), phenol (2a) and acetophenone (4a), with a conversion rate of 57.04%, which is significantly lower than the performance of the composite catalysts obtained in Examples 1 and 2. It is proved that the heterogeneous catalyst rich in defect sites and electron-deficient Bi species obtained under the optimized triethylamine ratio is the key to achieve efficient electrochemical hydrogenation of lignin. In addition, it can be seen from the corresponding linear sweep voltammetry curve ( Figure 8 ), the catalyst obtained in Comparative Example 1 requires a higher potential to achieve 100 mA cm -2 of current density.

[0077] Example 5

[0078] The electrocatalytic hydrogenation of 2-phenoxy-1-phenylethanol was carried out using Bi-(Et3N) prepared in Example 2 as a catalyst:

[0079] An "H" type electrolytic cell was used, with a graphite rod as the working electrode, a Pt sheet as the counter electrode, and Ag / AgCl as the reference electrode. A 0.25 M phosphotungstic acid solution was used as the cathode electrolyte, and a 0.2 M phosphoric acid solution was used as the anode electrolyte. The phosphotungstic acid and phosphoric acid solutions were 11 mL each. A constant current system was used, and the current density was 40 mA cm -2 , 0.02 g of catalyst and 2-phenoxy-1-phenylethanol were added for electrochemical hydrogenation, and the amount of 2-phenoxy-1-phenylethanol used was shown in Table 1. The temperature was set at 80°C and the electrolysis time was maintained for 1.5 hours.

[0080] The results show that the types of products obtained are the same as those in Example 4, and the conversion rates are shown in Table 1.

[0081] Table 1 Test results of Example 5

[0082]

[0083] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for electrocatalytic hydrogenation of lignin using a Bi-(Et3N) catalyst, characterized in that: Bi-(Et3N) catalyst and lignin model were added into the "H" type electrolytic cell, and the model was electrocatalytically hydrogenated under a constant current system.

2. The method for electrocatalytic hydrogenation of lignin using Bi-(Et3N) catalyst according to claim 1, characterized in that: The lignin model substance is 2-phenoxy-1-phenylethanol, and the mass ratio of the model substance to the catalyst is 0.4:1-5:

1.

3. The method for electrocatalytic hydrogenation of lignin using Bi-(Et3N) catalyst according to claim 1, characterized in that: Current density is 20~60 mA cm -2 .

4. The method for electrocatalytic hydrogenation of lignin using Bi-(Et3N) catalyst according to claim 1, characterized in that: The electrolytic cell uses a graphite rod as a working electrode, a Pt sheet as a counter electrode, Ag / AgCl as a reference electrode, a phosphotungstic acid solution as a cathode electrolyte, and phosphoric acid as an anode electrolyte.

5. The method for electrocatalytic hydrogenation of lignin using Bi-(Et3N) catalyst according to claim 4, characterized in that: The electrolyte concentrations of phosphotungstic acid were 0.25 M and phosphoric acid was 0.2 M.

6. The method for electrocatalytic hydrogenation of lignin using Bi-(Et3N) catalyst according to claim 1, characterized in that: The temperature of the electrochemical hydrogenation process is 80~100℃ and the time is 1.5~3 hours.

7. The method for electrocatalytic hydrogenation of lignin using Bi-(Et3N) catalyst according to claim 1, characterized in that: The preparation of the catalyst Bi-(Et3N) comprises the following steps: (1) Dissolve the metal Bi salt in deionized water, slowly add triethylamine, and stir overnight to obtain a milky white precipitate; (2) Transfer all the reaction liquid into a reactor, heat it in an air atmosphere, and then age and crystallize it; (3) After washing and centrifugation, a white precipitate was obtained, which was then dried in vacuum to obtain the heterogeneous Bi-(Et3N) catalyst.

8. The method for electrocatalytic hydrogenation of lignin using Bi-(Et3N) catalyst according to claim 7, characterized in that: In step (1), the metal Bi salt is Bi(NO3)3‧5H2O; and the molar ratio of the metal Bi salt to triethylamine is 1:3-1:

5.

9. The method for electrocatalytic hydrogenation of lignin using Bi-(Et3N) catalyst according to claim 7, characterized in that: In step (2), the heating temperature is 90-100° C. and the heating time is 6 hours.

10. The method for electrocatalytic hydrogenation of lignin using Bi-(Et3N) catalyst according to claim 7, characterized in that: In step (3), the vacuum drying temperature is 60° C. and the drying time is 12 hours.

Citation Information

Patent Citations

  • Use of substituted oxo tetrahydroquinoline sulfonamides or salts thereof for raising stress tolerance of plants

    CN106455565A

  • Method for preparing KA oil and derivatives of KA oil by electrocatalytic hydrogenation of lignin-based phenolic compounds

    CN108660479A

  • Composite materials comprising mechanical ligands

    CN111868146A

  • Method for preparing hexose derivatives

    US20090105466A1

  • Maleinated Derivatives

    US20190284152A1

Cited By

  • Method for preparing vanillin by depolymerizing lignin

    CN120794831A

  • Process for the preparation of vanillin from depolymerized lignin

    CN120794831B

  • Method for preparing cycloalkane compound by reducing lignin monophenol compound through electro-catalysis

    CN121896663A